2020
DOI: 10.5812/ijhls.106130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationship Between Levels of Self-Efficacy and Self-Care in Middle School Adolescents in Turkey

Abstract: : In this research it is aimed to investigate the relationship between the self-efficacy and self-care levels in adolescents which are aged between 11 - 15 years old. For this purpose, the socio-demographic characteristics of the students are utilized including, age, grade, gender, longest residence, family type, current residence location, family structure, academic success status, income-outcome balance, chronic diseases, education level of mother, education level of father, mother profession, father profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similarly, there was a statistically significant relationship between students' ages and their academic social, emotional, and general selfefficacy levels in the studies of Telef and Karaca, either (9). On the other hand, Coşkun and Yiğit was not found a statistically significant relationship between the ages of adolescents and their general self-efficacy levels (24). Based on the results of these studies, as the age of adolescents increases, their general selfefficacy decreases.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, there was a statistically significant relationship between students' ages and their academic social, emotional, and general selfefficacy levels in the studies of Telef and Karaca, either (9). On the other hand, Coşkun and Yiğit was not found a statistically significant relationship between the ages of adolescents and their general self-efficacy levels (24). Based on the results of these studies, as the age of adolescents increases, their general selfefficacy decreases.…”
Section: Discussionmentioning
confidence: 75%
“…The concept of quit addiction self-efficacy plays a criti-cal role in the amount of stimulant abuse (7). Self-efficacy was first used in the social learning theory to give meaning to a person's feelings regarding their ability and efficacy to produce, change, and control daily events (8). Wong and Longshore (9) found that higher levels of self-efficacy in abuse were related to the increased likelihood of quitting Heroin.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and emotional problems in adolescence are classified into two main categories of internalizing and externalizing behaviors. The former often manifests as anxiety/depression, isolation/depression, and somatic complaints, and the latter encompasses the behaviors that run counter to the wishes and expectations of one's social group and acquaintances and have an external direction (e.g., aggression and rule-breaking) (3,4).…”
Section: Introductionmentioning
confidence: 99%